Cracking the code: How procedural justice drives employee engagement in Nigerian banks - Paul, Salau, Odunayo; Adeola, Adegoke, Zainab; Oluwafunmilayo, Onayemi, Oluwakemi; Yemi, Ayandele, Blessing (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the influence of procedural justice on many aspects of employee engagement including affective, behavioral, cognitive and physical engagement specifically within the banking business in Nigeria. The sector has consistently faced difficulties in maintaining employee engagement with major issues such as high rates of absenteeism and turnover. Implementing an effective employee engagement strategy can help in retaining and developing a team that is prepared for the future, thereby reducing absenteeism and turnover. This study employed survey methodology and used stratified sampling techniques to choose participants. We collected the necessary data from primary sources. The study considered 209 of the 231 distributed questionnaires legitimate and appropriate. The results indicate that how employees perceive the fairness of procedures in the chosen bank has a substantial impact on their high levels of emotional, cognitive, physical and behavioral involvement. This demonstrates that ensuring fair treatment when creating clear and reliable policies and processes results in increased employee engagement. Banks should create an environment that promotes fairness by ensuring transparency and reliability in all rules and procedures to enhance overall satisfaction among workers and performance. It is possible to reduce high rates of absence and turnover resulting in a more stable and productive workforce by using these measures. This study highlights the significance of procedural justice in attaining greater employee engagement and offers significant insights for banks seeking to enhance their staff retention efforts.